WORKING WITH METHODS FOR DEVELOPING SPEAKING - Salomova Mohira Mirzakomilovna, (TADQIQOTLAR, 2025)
Abstract: Speaking is recognized as one of the most essential skills in language learning and communication. The act of speaking conveys not only words but also ideas, emotions, social relationships, and cultural values. In order to ensure effective communication and language proficiency, the development of speaking skills occupies a  significant  position  in  both  theoretical  and  practical  dimensions  of  language education.  The  ongoing  evolution  of  linguistic  research  and  pedagogic  strategies consistently demonstrates that speaking is a dynamic and multifaceted process, which requires a systematic and nuanced approach to teaching and learning. Within these dimensions, various methods have emerged, each with specific contributions to the overall improvement of learners’ speaking abilities.